Study on the Effective Method of Optimizing PCR-DGGE by adding PCR enhancers. Issue 1 (February 2020) - Zhao, Jirui; Wang, Shuang; Wei, Daiyan; Chen, Xiaoming; Xu, Yuan; Zhao, Wei; Ma, Nan; Zhan, Xianhui; Jia, Xiuyan; Sun, Meng; Liu, Jiahong
Abstract: PCR-based denaturing gradient gel electronic (PCR-DGGE) has become a frequently used method in the determination of bacteria community in water, soil and other habitats. However, the precision and the integrality of microbiology community by this approach should be reinforced and the key for this is optimization on PCR for which is the basis of PCR-DGGE. Aiming at this, PCR enhancer combinations were applied in both two amplification rounds of PCR-DGGE in this study. The results showed that many new bands were produced and originally weak bands were intensified after the addition of PCR enhancer combinations, particularly DBD-2 (1% DMSO, 0.4 M Betaine, 1mM DTT) in PCR amplification buffer system. Virtually all newly appeared bands in DGGE were probably derived from the bacteria with high GC% content (60%). Thus the major optimization on PCR-DGGE was PCR enhancer may contribute to decreasing annealing temperature and improving the PCR product yields of the high-GC%-contented bacteria. In conclusion, PCR enhancers could remarkably improve the amplification efficacy, particularly for using the complex and tiny environmental DNA or weaker bands from DGGE as PCR template, and furthermore increase the detected bacterial species in PCR-DGGE. Therefore we strongly proposed that the PCR enhancer combination be routinely applied in PCR-DGGE for the bacterial community determination.